Surface Modeling : High Accuracy and High Speed Methods. - Yue, Tian-Xiang (Applied ecology and environmental management., 2011)
Although GIS provides powerful functionality for spatial analysis, data overlay and storage, these spatially oriented systems lack the ability to represent temporal dynamics, which is a major impediment to its use in surface modeling. However, rapid development of computing technology in recent years has made real-time spatial analysis and real-time data visualization become realizable. Based on newly developed methods, Surface Modeling: High Accuracy and High Speed Methods explores solutions to big-error and slow-efficiency problems, two critical challenges have long plagued those working in.